Aplicação de extrato de algas marinhas em sistema de produção de girassol irrigado com água salina - Luna, Nayara Rochelli de Sousa (2019)
Considering the restrictions of water use in the Brazilian semi-arid region due to adverse climatic conditions, waters of inferior qualities (saline) can be a strategy to make agricultural production feasible in the region. In view that irrigation with saline waters can affect the development of plants due to the osmotic, toxic and nutritional effects, the use of seaweed extracts (Ascophyllum nodosum), appears as an alternative to improve the agronomic performance of cultures under abiotic stress. In this sense, the objective was to evaluate the foliar application of commercial extract of seaweed as a strategy to minimize the deleterious effects of salinity on the sunflower (Helianthus annuus). The experiment was carried out full sunlight, in the experimental area of the agrometeorological station of the Federal University of Ceará - UFC, Fortaleza. The design was randomized blocks, in a sub subsubdivided plots scheme, in which the plots were constituted by two cultivation cycles, the subplots by four levels of salinity (1.2, 3.0, 4.5 and 6.0 dS m-1) and sub-sub-plots by four doses of seaweed extract (0, 100, 150 and 200% of the extract manufacturer's recommendation). Were evaluated the contents of mineral elements, the growth, gas exchange, relative content of total chlorophyll, production and quality of production, as well as the evolution of soil electrical conductivity (EC). Salinity reduced leaf contents of all elements, except calcium (Ca) and sodium (Na), as well as inhibited growth, gas exchange, relative total chlorophyll content, production and quality of production, as well as to promote the growing accumulation of salts in soil. The seaweeds extract attenuated the deleterious effects of salinity on potassium (K) leaf content, stem diameter, internal diameter of the shoot, leaf area, shoot dry matter and total, relative chlorophyll content total, the productivity of achenes and the mass of 1,000 achenes up to level 3.0 dS m-1, since the algal extract had its effect inhibited on the highest levels of salinity evaluated (4.5 and 6.0 dS m-1). The most efficient doses of seaweeds extract were 100 and 150% of the product recommendation, noting that the maximum dose caused a reduction in leaf area, shoot dry matter, total dry matter and relative content of total chlorophyll.